Effects of Sentence Context on Phonemic Categorization of Natural and Synthetic Consonant-Vowel Tokens. Issue 1 (February 2014) - Hedrick, Mark S.; Lee, Ji Young; Harkrider, Ashley; Von Hapsburg, Deborah
The purpose was to assess if phonemic categorization in sentential context is best explained by autonomous feedforward processing or by top-down feedback processing that affects phonemic representation. 11 listeners with normal hearing, ages 20–50 years, were asked to label consonants in /pi/ – /ti/ consonant-vowel (CV) stimuli in 9-step continua. One continuum was derived from natural tokens and the other was synthetically generated. The CV stimuli were presented in isolation and in three sentential contexts: a neutral context, a context favoring /p/, and a context favoring /t/. For both natural and synthetic stimuli, the isolated and neutral context sentences yielded significantly more /t/ responses than sentence contexts primed for either /p/ or /t/. No other conditions were significantly different. Results did not show easily explainable semantic context effects. Instead, data clustering was more readily explained by top-down feedback processing affecting phonemic representation.